Community Empowerment Program in Overcoming the Problem of Disease in Tomajiko Kelurahan, Pulau Hiri District - Patilaiya, Hairudin La; Ishak, Sitti Nurhidayanti (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
Dengue Hemorrhagic Fever (DHF) is a problem for tropical countries such as Indonesia. The increasing number of deaths from this disease every year is an extraordinary event. To overcome this problem, the UMMU Ibm team attempted to carry out DHF control activities by disseminating DHF and the PSN (Mosquito Nest Eradication) movement with 3M plus, namely Draining, Closing and Burying. This program aims to increase public understanding of the risk of dengue disease as well as public awareness of clean lifestyles. The empowerment method used is literacy provision and mosquito nest eradication practice. This program is proven to be able to improve students’ understanding in eradicating mosquito nests that cause dengue fever. With this program, the people of Tomajiko sub-district, Hiri Island sub-district are expected to always keep the environment clean to avoid dengue fever. The results of this program are expected to be replicated by several villages around the Hiri archipelago that have the same demographic characteristics.